A dense NASICON sheet prepared by tape-casting and low temperature sintering. (10th July 2018) - Okubo, Keisuke; Wang, He; Hayashi, Katsuro; Inada, Miki; Enomoto, Naoya; Hasegawa, George; Osawa, Takashi; Takamura, Hitoshi
Abstract: Ceramic sheet of Na + ion-conducting solid electrolyte, Na3 Zr2 Si2 PO12 (NASICON), has been prepared by tape-casting method. Addition of 60Na2 O-10Nb2 O5 -30P2 O5 glass as a sintering aid is crucial for fabrication of fully-densified impermeable sheet. Otherwise the gas tightness is not achieved even sintered at 1200 °C. The best preparation condition is 5 or 10 wt% grass-addition with respect to NASICON and sintering at 1000–1100 °C, which is lower by 100–200 °C than the typical densification temperature of NASICON without the additive. A sample with a thickness of 35 μm and total conductivity of 4.4 × 10 −4  S cm −1 is obtained by 5 wt% glass addition and sintering at 1100 °C for 4 h. Graphical abstract: Image 1